Supplementation with cumulus cell masses improves the in vitro meiotic competence of porcine cumulus–oocytes complexes derived from small follicles. (30th March 2017) - Matsunaga, R; Funahashi, H
Contents: The present study was conducted to examine the supplemented effect of cumulus cell masses (CCMs) derived from middle follicle (MF; 3–6 mm diameter) on the morphology and the meiotic or developmental competence of oocytes from small follicles (SF; 1–2 mm diameter). The number of cumulus cells surrounding oocytes just after collection was also lower in cumulus–oocyte complexes (COCs) from SF than MF. The ooplasmic diameter of oocytes was significantly smaller in SF‐derived oocytes than MF‐derived ones before and after in vitro maturation (IVM), whereas the diameter significantly increased during the culture. Co‐culture of SF‐derived COCs with MF‐derived CCMs during IVM significantly improved the meiotic competence of the oocytes to the metaphase‐II stage. Furthermore, the ooplasmic diameter of SF‐derived COCs during IVM was increased to the similar size of MF‐derived those in the presence of MF‐derived CCMs. The abilities of oocytes to be penetrated, to form male pronuclear formation and to cleave or develop to the blastocyst stage were not affected by the co‐culture with CCMs. Electrophoretic analysis of CCM secretions clearly showed the presence of more protein(s) approximately 27.6 kDa in the conditioned medium when supplemented with MF‐derived CCMs. In conclusion, we demonstrate that supplementation with MF‐derived CCMs improves the ooplasmic diameter and meiotic competence of SF‐derived oocytes.